2013
DOI: 10.7314/apjcp.2013.14.11.6613
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in XRCC1 Gene, Alcohol drinking, and Risk of Colorectal Cancer: a Case-control Study in Jiangsu Province of China

Abstract: To evaluate the relationship between alcohol drinking, XRCC1 codon 194 and 399 polymorphisms and risk of colorectal cancer, we conducted a case-control study with 315 colorectal cancer cases (105 colon, 210 rectal) and 439 population-based controls in Jiangsu Province of China. The XRCC1 codon 194 and 399 genotypes were identified using polymerase chain reaction and restrictrion fragment length polymorphism methods (PCR-RFLP). A structured questionnaire was used to elicit detailed information. Odds ratios (ORs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
2
23
1
Order By: Relevance
“…Nowadays, A large of studies about Genetic polymorphisms (Fayaz;Gao et al, 2013;Li et al, 2013) has been reported, but in these studies, the relationship between the combined effect of different Gene loci has not been researched.To our knowledge, we have demonstrated that the relationship between combined effect of IL17A, IL17F genotypes and silicosis. And this is the first study shows that IL-17F 7488A/G polymorphism may contribute to the risk of silicosis.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, A large of studies about Genetic polymorphisms (Fayaz;Gao et al, 2013;Li et al, 2013) has been reported, but in these studies, the relationship between the combined effect of different Gene loci has not been researched.To our knowledge, we have demonstrated that the relationship between combined effect of IL17A, IL17F genotypes and silicosis. And this is the first study shows that IL-17F 7488A/G polymorphism may contribute to the risk of silicosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since the morbidity is rising, more and more researchers from different regions are paying close attention on colorectal cancer (Atrkar-Roushan et al, 2013;Gao et al, 2013;Heidarnia et al, 2013;Lohsiriwat et al, 2013;Madrigal-Bujaidar et al, 2013;Saeed et al, 2013). Among them, finding biomarkers for prognosis has long been a hotspot (Huang et al, 2012;Qian et al, 2012;Zhang et al, 2012;Chen et al, 2013;Cui et al, 2013;Dong et al, 2013;Sisik et al, 2013;Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Cancers are the most risk diseases which threaten our health at present, and there is rare indicator for early diagnosis. Breast and ovarian cancers are the most two frequent cancers of women worldwide, and the most lethal gynecological malignancy worldwide (Yip et al, 2006;Yip & Anderson, 2007;Gao et al, 2009;Khokher et al, 2012;Zhang et al, 2012). Early diagnosis and better prognosis of breast and ovarian cancers is still a challenge, and genetic factors have established a role in pathogenesis of breast and ovarian cancers (Yip et al, 2009;Gao et al, 2012;Jeschke et al, 2012;.…”
Section: Relationship Between the Prohibitin 3' Untranslated Region Cmentioning
confidence: 99%